2017
DOI: 10.1002/2016jb013864
|View full text |Cite
|
Sign up to set email alerts
|

Size limits for rounding of volcanic ash particles heated by lightning

Abstract: Volcanic ash particles can be remelted by the high temperatures induced in volcanic lightning discharges. The molten particles can round under surface tension then quench to produce glass spheres. Melting and rounding timescales for volcanic materials are strongly dependent on heating duration and peak temperature and are shorter for small particles than for large particles. Therefore, the size distribution of glass spheres recovered from ash deposits potentially record the short duration, high‐temperature con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 38 publications
4
39
0
Order By: Relevance
“…ECF2LAP was manufactured from pumice lapilli derived from a fall unit of the El Cajete series, the last major explosive event~75 ka from the Valles Caldera (Zimmerer et al, 2016). Although the size of the milled particles cannot be instrument controlled, they are small enough to be melted over the timescales of the current impulse (Wadsworth et al, 2017). Samples utilized here are from the later, violent Strombolian phase of the monogenetic eruption (Genareau et al, 2010;Valentine et al, 2007).…”
Section: Pseudo Ash Samplesmentioning
confidence: 99%
See 3 more Smart Citations
“…ECF2LAP was manufactured from pumice lapilli derived from a fall unit of the El Cajete series, the last major explosive event~75 ka from the Valles Caldera (Zimmerer et al, 2016). Although the size of the milled particles cannot be instrument controlled, they are small enough to be melted over the timescales of the current impulse (Wadsworth et al, 2017). Samples utilized here are from the later, violent Strombolian phase of the monogenetic eruption (Genareau et al, 2010;Valentine et al, 2007).…”
Section: Pseudo Ash Samplesmentioning
confidence: 99%
“…Although the preexperimental samples were analyzed with the laser diffractometer, the postexperimental samples were analyzed with the Hydro Sight™ peripheral component (video camera), and thus, each different colored curve in (b) and (c) represents a single snapshot of the dispersion when an anomaly (particle of unusual size or shape) is detected. Additionally, modeling studies (Wadsworth et al, 2017) have shown that the timescales of lightning discharge (milliseconds) require grains to be below a certain size (<150 μm) for melting to occur, which is why this size range was examined. Raw data for the curves shown in (a) can be found in the supporting information (Tables S1-S4). samples were available from both eruptions, during which lightning was documented, and both were deposited at a similar distance from the vent (~75 km).…”
Section: Natural Ash Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the knowledge of cooling time scales of pyroclasts is important for better interpretation of pre-to post-eruptive processes. Additionally, interphase heat transfer between pyroclast or lava and surrounding air is an important parameter in subaerial lava flow, eruption column, and pyroclastic flow modeling (e.g., Andrews & Manga, 2012;Dobran et al, 1993;Dufek & Bergantz, 2007;Dufek, 2016;Harris et al, 2007;Patrick et al, 2004;Thomas & Sparks, 1992;Valentine & Wohletz, 1989;Vanderkluysen et al, 2012;Wadsworth et al, 2017;Woods & Bursik, 1991).…”
Section: Introductionmentioning
confidence: 99%